2021
DOI: 10.1111/exd.14473
|View full text |Cite
|
Sign up to set email alerts
|

Important role of mechanical microenvironment on macrophage dysfunction during keloid pathogenesis

Abstract: Keloid is a chronic inflammation-associated skin fibrosis with overabundant immune cells and extracellular matrix (ECM). 1 Keloids appear to share similar features with tumors such as progressive uncontrolled growth, invasive ability and high rates of recurrence. 2,3 Topological, environmental and patient-related factors have been considered as the main pathogenetic factors of keloids. 4 In recent years, mechanical microenvironment, an important topological factor, has received increased attention for mediatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Transcriptome analysis showed that the core differentially expressed genes related to collagen synthesis play a vital role in the pathogenesis of keloids, including COL1A, COL1A2, COL5A2, and COL3A1. The analysis of the keloid immune microenvironment revealed the infiltration of immune cells around fibroblasts, which directly or indirectly affected the proliferation of fibroblasts ( Zhou et al, 2021 ). The expression of NNMT, AOX1, PLOD1, PLOD2, and PLOD3 at the transcription level is consistent with the metabolome sequencing data ( Supplementary Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analysis showed that the core differentially expressed genes related to collagen synthesis play a vital role in the pathogenesis of keloids, including COL1A, COL1A2, COL5A2, and COL3A1. The analysis of the keloid immune microenvironment revealed the infiltration of immune cells around fibroblasts, which directly or indirectly affected the proliferation of fibroblasts ( Zhou et al, 2021 ). The expression of NNMT, AOX1, PLOD1, PLOD2, and PLOD3 at the transcription level is consistent with the metabolome sequencing data ( Supplementary Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…M2 macrophages are disproportionally elevated in keloid lesions ( 69 – 72 , 74 ), in part due to local enrichment of Th2 cytokines. Although not yet verified, M2 dominance has also been linked to macrophage sensitivity to mechanical signals, including skin tension and stiffness ( 42 ). M2 macrophages initiate wound closure via secretion of TGF-β1, a potent inducer of both fibroblast proliferation and their differentiation into myofibroblasts ( 115 ).…”
Section: The Roles Of Immune Cells In Keloid Formationmentioning
confidence: 99%
“…It is believed that pathological scars are caused by excessive and persistent inflammation, and the intensity of inflammation is positively correlated with the final scar size ( Huang et al, 2014 ). Various inflammatory cells, including ( Zhou et al, 2021 ), mast cells ( Bagabir et al, 2012 ), lymphocytes ( Chen et al, 2018 ), and monocytes ( Limandjaja et al, 2019 ), have been reported to be involved in keloid formation. Among these, macrophages are important cells that initiate an inflammatory response during wound healing and lead to excessive spreading of inflammation.…”
Section: Keloid Pathogenesis Studymentioning
confidence: 99%